2021
DOI: 10.1093/biolre/ioab119
|View full text |Cite
|
Sign up to set email alerts
|

Low CLOCK and CRY2 in 2nd trimester human maternal blood and risk of preterm birth: a nested case-control study†

Abstract: Previous studies have observed an association between maternal circadian rhythm disruption and preterm birth (PTB). However, the underlying molecular mechanisms and the potential of circadian clock genes to serve as predictors of PTB remain unexplored. We examined the association of 10 core circadian transcripts in maternal blood with spontaneous PTB (sPTB) vs term births using a nested case–control study design. We used a public gene expression dataset (GSE59491), which was nested within the All Our Babies (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…3 B). Interestingly, the Two-way ANOVA showed that gestation length trended towards a reduction in CLOCK [F(1,5) = 6.020, p = 0.0577], supporting our previous work that identified that PTB correlated with reduced maternal blood CLOCK mRNA 56 .
Figure 3 CLOCK protein is reduced in term PE placenta.
…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…3 B). Interestingly, the Two-way ANOVA showed that gestation length trended towards a reduction in CLOCK [F(1,5) = 6.020, p = 0.0577], supporting our previous work that identified that PTB correlated with reduced maternal blood CLOCK mRNA 56 .
Figure 3 CLOCK protein is reduced in term PE placenta.
…”
Section: Resultssupporting
confidence: 83%
“…Indeed, the fact that PF670462 upregulates PER1/2/3 might mask a specific effect of PER3 on HTR-8 cell migration; however, due to experimental constraints, we were unable to test whether PER3 downregulation would decrease HTR-8 migration. Another possibility is that PER3 might signal gestation length, as supported by our maternal blood study 56 , and preliminary GWAS study 74 , both of which suggest that deregulated or low PER3 levels might be linked to gestation length and predispose women to PTB. Mechanisms that PER3 may engage to signal gestation length remain unknown.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Studies in mice have shown that loss of molecular clock function reduces reproductive success ( Miller et al, 2004 ; Kennaway et al, 2012 ; Sen and Hoffmann, 2020 ; Yaw et al, 2020 ; Hoffmann et al, 2021 ), and is associated with increased risk of mis-timed birth and dystocia ( Ratajczak et al, 2012 ; Miller and Takahashi, 2014 ). Our recent studies in human placenta indicate that co-alterations of the molecular clock mRNAs NR1D2 , CLOCK and PER3 are significantly associated with term preeclampsia ( Zhou et al, 2022 ), whereas co-alteration of CLOCK and CRY2 at the mRNA levels in second trimester maternal blood are significantly associated with an increased risk of sPTB ( Zhou et al, 2021a ). However, the expression pattern of core molecular clock genes in placentas of sPTB vs term births, as well as the underlying mechanism(s) are still unknown.…”
Section: Introductionmentioning
confidence: 99%